Family-centred care for hospitalised children aged 0-12 years (Review) - Shields, L.; Zhou, Huaqiong; Pratt, J.; Taylor, M.; Hunter, J.; Pascoe, E. (John Wiley & Sons, 2012)
Background: This is an update of the Cochrane systematic review of family-centred care published in 2007 (Shields 2007). Family-centred care (FCC) is a widely used model in paediatrics, is thought to be the best way to provide care to children in hospital and is ubiquitous as a way of delivering care. When a child is admitted, the whole family is affected. In giving care, nurses, doctors and others must consider the impact of the child’s admission on all family members. However, the effectiveness of family-centred care as a model of care has not been measured systematically. Objectives: To assess the effects of family-centred models of care for hospitalised children aged from birth (unlike the previous version of the review, this update excludes premature neonates) to 12 years, when compared to standard models of care, on child, family and health service outcomes. Search methods: In the original review, we searched up until 2004. For this update, we searched: the Cochrane Central Register of Controlled Trials (CENTRAL,The Cochrane Library, Issue 12 2011); MEDLINE (Ovid SP); EMBASE (Ovid SP); PsycINFO (Ovid SP); CINAHL(EBSCO Host); and Sociological Abstracts (CSA). We did not search three that were included in the original review: Social Work Abstracts, the Australian Medical Index and ERIC. We searched EMBASE in this update only and searched from 2004 onwards. There was no limitation by language. We performed literature searches in May and June 2009 and updated them again in December 2011.Selection criteria: We searched for randomised controlled trials (RCTs) including cluster randomised trials in which family-centred care models are compared with standard models of care for hospitalised children (0 to 12 years, but excluding premature neonates). Studies had to meet criteria for family-centredness. In order to assess the degree of family-centredness, we used a modified rating scale based on a validated instrument, (same instrument used in the initial review), however, we decreased the family-centredness score for inclusion from 80%to50% in this update. We also changed several other selection criteria in this update: eligible study designs are now limited to randomised controlled trials (RCTs) only; single interventions not reflecting a FCC model of care have been excluded; and the selection criterion whereby studies with inadequate or unclear blinding of outcome assessment were excluded from the review has been removed. Data collection and analysis: Two review authors undertook searches, and four authors independently assessed studies against the review criteria, while two were assigned to extract data. We contacted study authors for additional information.Main results: Six studies found since 2004 were originally viewed as possible inclusions, but when the family-centred score assessment was tested, only one met the minimum score of family-centredness and was included in this review. This was an unpublished RCT involving288 children post-tonsillectomy in a care-by-parent unit (CBPU) compared with standard inpatient care. The study used a range of behavioural, economic and physical measures. It showed that children in the CBPU were significantly less likely to receive inadequate care compared with standard inpatient admission, and there were no significant differences for their behavioural outcomes or other physical outcomes. Parents were significantly more satisfied with CBPU care than standard care, assessed both before discharge and at7 days after discharge. Costs were lower for CPBU care compared with standard inpatient care. No other outcomes were reported. The study was rated as being at low to unclear risk of bias. Authors’ conclusions: This update of a review has found limited, moderate-quality evidence that suggests some benefit of a family-centred care intervention for children’s clinical care, parental satisfaction, and costs, but this is based on a small dataset and needs confirmation in larger RCTs. There is no evidence of harms. Overall, there continues to be little high-quality quantitative research available about the effects of family-centred care. Further rigorous research on the use of family-centred care as a model for care delivery to children and families in hospitals is needed. This research should implement well-developed family-centred care interventions, ideally in randomised trials. It should investigate diverse participant groups and clinical settings, and should assess a wide range of outcomes for children, parents, staff and health services.